Pengaruh Likuiditas dan Solvabilitas Terhadap Pertumbuhan Laba Bersih pada PT. Astra Graphia Tbk - Muhamad Asri; Nurul Huda; M. Rimawan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to determine the effect of liquidity as measured by the Current Ratio (CR) and solvency as measured by the Debt to Equity Ratio (DER) on net profit growth at PT Astra Graphia Tbk during the period 2015–2024. This research employed a quantitative approach with an associative research design. The data used were secondary data obtained from the annual financial statements of PT Astra Graphia Tbk for the period 2015–2024. Data analysis techniques included classical assumption tests, multiple linear regression analysis, correlation coefficient, coefficient of determination, t-test, and F-test using SPSS version 22. The results showed that the Current Ratio (CR) partially had no significant effect on net profit growth, with a significance value of 0.648 > 0.05. The Debt to Equity Ratio (DER) also had no significant partial effect on net profit growth, with a significance value of 0.397 > 0.05. Simultaneously, the Current Ratio (CR) and Debt to Equity Ratio (DER) had no significant effect on net profit growth, with a significance value of 0.646 > 0.05. The coefficient of determination (R²) was 0.117, indicating that liquidity and solvency variables explained only 11.7% of net profit growth, while the remaining 88.3% was influenced by other factors outside the scope of this study.